Acylation of lysine 983 is sufficient for toxin activity of Bordetella pertussis adenylate cyclase. Substitutions of alanine 140 modulate acylation site selectivity of the toxin acyltransferase CyaC - Basar, T; Havlícek, V; Bezousková, S; Hackett, M; Sebo, P (The Journal of biological chemistry, 2001)
The capacity of adenylate cyclase toxin (ACT) to penetrate into target cells depends on post-translational fatty-acylation by the acyltransferase CyaC, which can palmitoylate the conserved lysines 983 and 860 of ACT. Here, the in vivo acylating capacity of a set of mutated CyaC acyltransferases was characterized by two-dimensional gel electrophoresis and mass spectrometric analyses of the ACT product. Substitutions of the potentially catalytic serine 20 and histidine 33 residues ablated acylating activity of CyaC. Conservative replacements of alanine 140 by glycine (A140G) and valine (A140V) residues, however, affected selectivity of CyaC for the two acylation sites on ACT. Activation by the A140G variant of CyaC generated a mixture of bi- and monoacylated ACT molecules, modified either at both Lys-860 and Lys-983, or only at Lys-860, respectively. In contrast, the A140V CyaC produced a nearly 1:1 mixture of nonacylated pro-ACT with ACT monoacylated almost exclusively at Lys-983. The respective proportion of toxin molecules acylated at Lys-983 correlated well with the cell-invasive activity of both ACT mixtures, which was about half of that of ACT fully acylated on Lys-983 by intact CyaC. These results show that acylation of Lys-860 alone does not confer cell-invasive activity on ACT, whereas acylation of Lys-983 is necessary and sufficient.
Keywords: hemolýza; Hemolysis; acylace; mutace; vazebná místa; Virulence Factors, Bordetella; posttranslační úpravy proteinů; 2D gelová elektroforéza; acyltransferasy; Palmitic Acid; molekulární sekvence - údaje; Amino Acid Sequence; Electrophoresis, Gel, Two-Dimensional; Adenylate Cyclase Toxin; Acylation; Sequence Alignment; ovce; Mass Spectrometry; kyselina palmitová; Protein Processing, Post-Translational; Sheep; sekvenční seřazení; Amino Acid Substitution; Lysine; lysin; Bordetella pertussis; peptidové fragmenty; Binding Sites; substrátová specifita; Animals; Acyltransferases; Substrate Specificity; zvířata; substituce aminokyselin; sekvence aminokyselin; erytrocyty; Erythrocytes; Molecular Sequence Data; hmotnostní spektrometrie; Mutation; adenylátcyklasový toxin; Peptide Fragments; Histidine; Serine; faktory virulence rodu Bordetella; serin; histidin